Ascenso y caída de las bestias: evolución de la alegoría animal en la Edad Media - Claudia Inés Raposo (Medievalista)
Most of the history of medieval thought was influenced by Platonism and the reworkings that the Latin and Greek Fathers made of Plato's doctrines. The worldview resulting from this thought considered that each manifestation of the sensible world, while participating in the nature of God, was the opportunity to access transcendent knowledge. Among these manifestations, animals played a prominent role. Zoological knowledge inherited from classical antiquity was given new meaning and enriched through an exegesis that transformed beasts into examples that illustrated aspects of Christian doctrine or provided models of moral conduct. The Physiologus and its derivatives, the medieval bestiaries are an example of this interpretive practice, which for these texts was based primarily on allegory. In this article, we propose to see how and with what objectives it was applied to animals and we will inquire about the evolution of animal symbolism in the framework of the decline of Platonism and the rise of Aristotelianism in the last centuries of the Middle Ages. For this, we will analyze a brief corpus, composed of the beaver, the weasel, the oyster and the pearl, and the elephant.